ANALYSIS EFFECT OF GOVERNMENT REVENUES ON INDONESIA'S ECONOMIC GROWTH ON 1991-2020 - Yunita, Nuraeni; Indrawati, Lucia Rita (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
The objective of this study is to investigate the impact that exports, imports, and tax revenues have had on the rate of economic growth in Indonesia between the years 1991 and 2020. This study follows a quantitative approach to research methodology. The data that were used in this analysis were secondary data that were gathered from the Ministry of Finance of the Republic of Indonesia and the World Bank. The data for this study were compiled by using time series data from 1991 all the way up until 2020. The approach of using Ordinary Least Squares with an Error Correction Model as the analytical model that is applied is utilized. According to the findings of this study, both long-term and short-term variables related to exports have an effect that is detrimental to the economic growth of Indonesia. Both long-term and short-term changes in Indonesia's imports have no effect on the country's overall economic growth. Further, the impact of long-term tax revenue on economic growth in Indonesia is negative, while the impact of short-term tax revenue is meaningless to the country's overall development.